POTENTIAL SIGNIFICANCE OF BRADYKININ 2 RECEPTOR GENOTYPING IN KIDNEY TRANSPLANT RECIPIENTS - Danković, Katarina; Stefanović, Nikola; Veličković-Radovanović, Radmila; Mitić, Branka; Paunović, Goran; Cvetković, Mina; Cvetković, Tatjana (Acta medicae Medianae, 2021)
Bradykinin (BK) is considered to exert renoprotective and cardioprotective effects. Most of its biological effects are mediated by the activation of BK type 2 receptor (B2R), which level of expression is influenced by insertion/deletion (+9/-9) gene polymorphism. The aim of this study was to investigate the potential influence of B2R +9/-9 gene polymorphism on kidney function and blood pressure in kidney transplant recipients (KTRs) within the first year after kidney transplantation. Secondary, the study analyzed the correlation between hypertensive status and graft function, with respect to the B2R +9/-9 gene polymorphism. The pharmacogenetic study included 95 KTRs with clinical and biochemical parameters evaluated in three time-points (3rd, 6th, 12th month). The graft function was assessed using the estimated glomerular filtration rate (eGFR), while systolic (SBP), diastolic (DBP), and mean blood pressure (MAP) were used as parameters for the evaluation of blood pressure control. The carriers of both -9 alleles had more stable graft function compared to both heterozygotes and +9/+9 genotype carriers not only in the early (up to 6 months), but as well in the late post-transplantation period (beyond 6 months). Also, the -9/-9 genotype carriers showed a tendency to significantly decrease MAP, SBP, and DBP in the observed period, whereby only in this genotype group the interrelation between hypertensive status and graft function had been demonstrated. In conclusion, genotyping of B2R +9/-9 gene polymorphism alongside with biochemical and clinical parameters may enable the identification of patients at high risk for a more prompt decline of graft function.